Library as a Pillar of Wisdom in the Indian Knowledge System: Evolution, Preservation, and Dissemination of Knowledge (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The Indian Knowledge System (IKS) represents one of the oldest, most diverse, and most profound intellectual traditions in the world. From the oral transmission of the Vedas to the establishment of ancient manuscript libraries and modern digital repositories, libraries have played a vital role in preserving, organizing, and disseminating knowledge. This research article examines the historical evolution of libraries in India, their philosophical foundation within the Indian Knowledge System, and their critical role in safeguarding religion, history, culture, and scientific traditions. The study highlights how the destruction of libraries leads to irreversible cultural loss and discusses the transformation of libraries from manuscript repositories to modern information dissemination centers. The article concludes with suggestions for strengthening libraries as cultural and knowledge preservation institutions in contemporary India.